Peningkatan Kompetensi Profesi Guru Memanfaatkan Media Pembelajaran Berbasis Information Technology melalui In House Training di SD Negeri 5 Gunuang Malintang - Jasmiati, Jasmiati (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2019)
This School Action Research is intended to improve teachers’ competence in using IT-Based Learning Media. The study was conducted at SDN 05 Gunuang Malintang with 12 research subjects. The results of the data analysis which was collected through observation, interviewing, and tests indicated that the teacherss’ ability in utilizing IT-based learning media can be improved through IHT. The steps of IHT activities are as follows: (1). Distributing the initial test to the teachers, (2) The teachers worked on the initial test to determine the ability to use and utilize IT as a learning medium. (3) Providingmaterial perceptions about the use of IT-based learning media. (4) Providing services and guidance to teachers about the use of IT. (5) Providing opportunities for teachers to create and innovate in utilizing IT as a learning media. (6). Providing services and guidance to teachers during IHT. (7). Giving the final test. The results of this study are the teachers ability to utilize IT-based learning media can be improved through IHT at SDN 05 Gunung Malintang.